A bibliometric analysis of the link between women leadership and corruption: A review of the literature from 2009 to 2023 - Nyongesa, Wesonga Justus; Westhuizein, Johan Van Der (International Journal of Innovative Research and Scientific Studies, 2025)
The recent focus on women’s leadership emphasizes the global movement towards gender equality in multiple sectors, underscoring the significance of inclusive governance and decision-making processes. Corruption continues to be a significant barrier to economic growth, social justice, and political stability. Women are underrepresented in leadership roles, occupying only 24% of parliamentary seats worldwide and 7.4% of CEO positions in Fortune 500 companies. This study aims to investigate the relationship between increased female leadership and the incidence of corruption. This study conducts a bibliometric analysis of 125 scholarly articles to examine the literature on the intersection of gender, leadership, and corruption from 2009 to 2023. The findings indicate a notable research gap, especially within the Global South, where African nations are inadequately represented in studies concerning corruption and leadership. Furthermore, the funding allocated for research in this area is insufficient, hindering the formulation of evidence-based policies. Current research primarily addresses political governance, education, and socioeconomic factors, while neglecting critical areas such as gender disparity, economic development, business ethics, violence, and organizational management concerning women’s leadership and corruption. Empirical studies play a crucial role in informing policy development, bridging knowledge gaps, and directing future research efforts.